EXTH-45. THERAPEUTIC EFFICACY OF MUTANT ISOCITRATE DEHYDROGENASE 1 (IDH1) INHIBITOR SYC-435 WITH STANDARD THERAPY IN PATIENT-DERIVED IDH1 MUTANT GLIOMA XENOGRAFT MOUSE MODELS. (11th November 2019) - Kogiso, Mari; Qi, Lin; Zhang, Huiyuan; Braun, Frank; Du, Yuchen; Huang, Lei; Guo, Lei; Huang, Yulun; Lindsay, Holly B; Zhao, Sibo; Injac, Sarah; Baxter, Patricia; et al.
Abstract: Mutation in isocitrate dehydrogenase 1 (IDH1) occurs in >70% of WHO grade II/III astrocytomas, oligodendrogliomas and secondary glioblastoma. The mutant enzyme catalyzes the reduction of α-ketoglutaric acid to D-2-hydroxyglutaric acid, leading to cancer initiation. In this study, we examined therapeutic efficacy of SYC-435 (1-hydroxypyridin-2-one), a newly developed mutant IDH1inhibitor, in IDH1 mutant gliomas. IDH1 R132H mutation (homozygous) was detected in BT142 anaplastic oligoastrocytoma (AOA) and R132C mutation (mutant allele frequency 39–50%) in V0914AOA by pyrosequencing. Suppression of cell growth by SYC-435 was observed with more sensitive of mutant over wild-type IDH1. Patient-derived orthotopic xenograft mouse models of BT142AOA and V0914AOA were treated with vehicle, SYC-435 (15 mg/kg/day x 28 days), temozolomide (50 mg/kg/day x 5 days)/fractionated radiation (2 Gy/day x 5 days) (standard therapy), and SYC-435/standard therapy starting 2 weeks after intracranial tumor implantation. Log rank analysis showed SYC-435 alone did not alter survival times. Although standard therapy significantly prolonged survival times in both models (P< 0.0005), SYC-435/standard therapy further extended survival times (P< 0.05) in V0914AOA and exhibited similar trend in BT142AOA. Elevation of 2-HG/α-KG ratio and methylation of H3K4/H3K9 in V0914AOA tumor compared to wild-type model was detected at the end of treatments. SYC-435 with/without standard therapy tended to reduce 2-HG/α-KG ratio and dramatically reduced methylation of H3K4/H3K9. RNA-seq analysis showed sirtuin signaling pathway, mitochondrial dysfunction and oxidative phosphorylation pathways with mitochondrial DNA (mtDNA) encoded molecules were highly affected by all treatments. However, mtDNA regulation did not correlate to survival benefits. In conclusion, SYC-435 possesses anti-tumor effects that are more sensitive in IDH1 mutant gliomas and generated strong synergistic activities with standard therapies for survival benefits with reduced methylation of H3K4/H3K9. Treatments significantly affected mtDNA but significance to survival benefits remains to be elucidated. Our data support the clinical testing of SYC-435 in patients with IDH1 mutant glioma.